Bank and sovereign debt risk connection - Matthieu Darracq Pariès; Ester Faia; Diego Rodriguez Palenzuela (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
Euro area data show a positive connection between sovereign and bank risk, which increases with banks' and sovereign long run fragility. We build a macro model with banks subject to moral hazard and liquidity risk (sudden deposit withdrawals): banks invest in risky government bonds as a form of capital buffer against liquidity risk. The model can replicate the positive connection between sovereign and bank risk observed in the data. Central bank liquidity policy, through full allotment policy, is successful in stabilizing the spiraling feedback loops between bank and sovereign risk.
Keywords: E5; G3; E6; 330; liquidity risk; sovereign risk; capital regulations